Representasi Loneliness Tokoh Ibu dalam Novel Bila Esok Ibu Tiada: Kajian Psikologi Sastra (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Loneliness is a subjective psychological phenomenon characterized by feelings of alienation, emptiness, and dissatisfaction with the quality of an individual's social relationships. This phenomenon is experienced not only by individuals who live alone or experience social isolation, but also by individuals within a family environment, including women who play the role of mother. The novel Bila Esok Ibu Tiada (When Tomorrow Mother is Gone) presents an in-depth representation of the inner life of a mother who experiences loneliness in the midst of a structurally intact family relationship. This study aims to examine the representation of loneliness in the mother character in the novel Bila Esok Ibu Tiada through a literary psychology approach. The research method used is descriptive qualitative with literary text analysis techniques. The results show that the mother's loneliness is represented through emotional alienation within the family, lack of support from her partner and children, weak interpersonal communication, inner conflict due to the sacrifice of her maternal role, and social pressure attached to the construction of the mother's role. Loneliness in this novel not only serves as a depiction of individual psychological conditions, but also as a social critique of family structures and cultures that tend to normalize mothers' emotional sacrifices without providing space for the fulfillment of their psychological needs.